Small Business Innovation in Nigeria: A Seamless Technology Integration Approach - Balogun, Ebenezer (Journal of Technology Management and Business, 2025)
The increasing adoption of digital technologies offers considerable opportunities for small businesses in emerging economies to strengthen their capacity for innovation. However, the effective integration of these technologies into organisational processes remains a critical challenge. This study investigates how seamless technological integration influences organisational innovation within the context of small businesses in Nigeria, an emerging market economy. It focuses on four key dimensions namely process integration, system process integration, system integration, and data consistency. The data were collected using structured questionnaires administered to micro and small entrepreneurs in Kwara State, Nigeria. PLS-SEM was used to analyse the relationships between the identified dimensions of technological integration and organisational innovation. The results show that system integration has a significant positive influence on organisational innovation, followed by data consistency and process integration. These results emphasise the critical role of integrated technological infrastructures in improving innovation outcomes for small businesses operating in resource-constrained environments. In light of these findings, micro and small business owners should prioritise the adoption of integrated technological systems as a central component of their innovation strategies.